What is hot and new in basic and translational science in liver transplantation in 2023?: report of the basic and Translational Research Committee of the International Liver Transplantation Society - Bonaccorsi-Riani, Eliano; Ghinolfi, Davide; Czigány, Zoltán; Dondossola, Daniele; Emamaullee, Juliet; Yuksel, Muhammed; Boteon, Yuri L.; Al-Adra, David; Ho, Cheng-Maw; Abdelrahim, Maen; Pang, Li; Barbas, Andrew; et al. (Transplantation, 2024)
The 2023 Joint Annual Congress of the International Liver Transplantation Society, European Liver and Intestine Transplant Association, and Liver Intensive Care Group of Europe were held in Rotterdam, the Netherlands, from May 3 to 6, 2023. This year, all speakers were invited to attend the Congress in person for the first time since the COVID-19 pandemic. The congress was attended by 1159 registered delegates from 54 countries representing 5 continents, with the 10 countries comprising the bulk of the delegates. Of the 647 abstracts initially submitted, 542 were eventually presented at the meeting, coming from 38 countries (mainly North America, Europe, and Asia) and 85% of them (462 abstracts) came from only 10 countries. Fifty-three (9.8%) abstracts, originated from 17 countries, were submitted under the Basic/Translational Scientific Research category, a similar percentage as in 2022. Abstracts presented at the meeting were classified as (1) ischemia and reperfusion injury, (2) machine perfusion, (3) bioengineering and liver regeneration, (4) transplant oncology, (5) novel biomarkers in liver transplantation, (6) liver immunology (rejection and tolerance), and (7) artificial intelligence and machine learning. Finally, we evaluated the number of abstracts commented in the Basic and Translational Research Committee-International Liver Transplantation Society annual reports over the past 5 y that resulted in publications in peer-reviewed journals to measure their scientific impact in the field of liver transplantation.
Gesehen am 24.06.2025